The Influence of Service Quality and Customer Experience on Customer Loyalty with Customer Satisfaction as an Intervening Variable: A Study of IndiHome Users in the Community of Pandau Jaya Village - Rachmad, Ferizal; Dermawan, Eryanda (International Journal of Business and Information Technology, 2025)
IndiHome is an integrated digital service that provides fiber-optic internet, landline telephone, and IPTV. Since July 1, 2023, it has been integrated into Telkomsel under the Fixed Mobile Convergence (FMC) strategy. This study aims to analyze the influence of Service Quality and Customer Experience on Customer Loyalty, with Customer Satisfaction serving as a mediating variable, among IndiHome users in Pandau Jaya Village, Siak Hulu District, Kampar Regency. Employing a quantitative approach and utilizing SmartPLS 3.3.3 for data analysis, the findings indicate that both Service Quality and Customer Experience have a significant positive effect on Customer Satisfaction. Furthermore, Customer Satisfaction significantly affects Customer Loyalty. However, the direct effects of Service Quality and Customer Experience on Customer Loyalty are not statistically significant. The results suggest that both independent variables exert significant indirect effects on loyalty through satisfaction. The model accounts for 86.9% of the variance in Customer Satisfaction and 55.4% of the variance in Customer Loyalty